Penyuluhan Perilaku Hidup Bersih dan Sehat (PHBS) bagi Siswa- Siswi SD 16 Kabupaten Sumbawa - Nur Arifatus Sholihah; Iga Maliga; Asri Reni Handayani; Herni Hasifah (Pusat Riset dan Inovasi Nasional, 2023)
. Clean and Healthy Living Behavior (PHBS) refers to efforts and actions taken by individuals, families, groups, and communities to create conditions that support health and maintain and improve health status. Teaching Clean and Healthy Living Behavior to elementary school children not only helps prevent disease and maintain their health, but also forms healthy living habits that they will carry throughout their lives. The purpose of this community service is to increase knowledge and awareness of Clean and Healthy Living Behavior to students of SD 16 Sumbawa. The implementation method used is the lecture method, discussion, and direct observation to the place of service. The participants involved were 20 students of SD 16 Sumbawa on Wednesday, Mei 10, 2023. The results showed that before counseling, 60% (12 students) of the 20 respondents had poor initial knowledge, but after counseling, the number of students with high knowledge increased to 75% (15 students). This means that counseling on Clean and Healthy Living Behavior for SD 16 Sumbawa students can increase knowledge and awareness of the importance of implementing Clean and Healthy Living Behavior.